1995
DOI: 10.1159/000282746
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer-Induced Oncogenic Hypophosphatemic Osteomalacia

Abstract: A 6 5-year-old male with prostate carcinoma showed mild hypocalcemia of 7.9 mg/dl, marked hypophosphatemia of 1.7 mg/dl, hyperphosphaturia (tubular reabsorption of phosphorus 43% and tubular threshold for phosphorus of 0.6 mg/dl), low serum 1,25 (OH)2D level of less than 5 pg/ml and osteomalacia indicated by a marked increase of relative osteoid volume and fractional formation rate in the undecalcifïed section. Oncogenic osteomalacia due to prostatic carcinoma with suppression of 1,25 (OH)2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…These findings strongly suggest that the neoplasm produced a phosphatonin other than FGF23. [3][4][5][6] There is also a recent report of a patient with TIO secondary to disseminated colonic adenocarcinoma, in which the colonic carcinoma was FGF23 immunoreactive using a more recently developed antibody. 10,[34][35][36] It is also notable that the ovarian serous carcinoma, from a patient with disseminated disease, elevated serum FGF23 levels, and clinical TIO, was negative for FGF23 mRNA expression by CISH.…”
Section: Discussionmentioning
confidence: 99%
“…These findings strongly suggest that the neoplasm produced a phosphatonin other than FGF23. [3][4][5][6] There is also a recent report of a patient with TIO secondary to disseminated colonic adenocarcinoma, in which the colonic carcinoma was FGF23 immunoreactive using a more recently developed antibody. 10,[34][35][36] It is also notable that the ovarian serous carcinoma, from a patient with disseminated disease, elevated serum FGF23 levels, and clinical TIO, was negative for FGF23 mRNA expression by CISH.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of TIO are related to mesenchymal neoplasms, while TIO secondary to epithelial neoplasms is rarely reported, particularly in cases of prostate carcinoma [2]. Although different kinds of mesenchymal neoplasms were thought to cause TIO, Folpe et al (2004) revealed that histologically uniform neoplasms known as phosphaturic mesenchymal tumors (PMTs) are the main cause of TIO associated with mesenchymal neoplasms [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…2-4,6-10,12,14-16,18-22,24-26,28-34,37,38,41-46,49-57,59-69, 71-79,82-90,92-107,109,110 The overwhelming majority of cases of OO are associated with soft tissue or bone neoplasms, although a small number of cases of OO have been reported in association with syndromes such as neurofibromatosis-1 38 and McCune-Albright syndrome, 46,108 and in patients with carcinomas. 17,53,55 It has been shown that OO-associated mesenchymal tumors overexpress fibroblast growth factor-23 (FGF-23), a recently described protein capable of inhibiting renal tubular epithelial phosphate transport, 1 and this is now thought to be the mechanism underlying most cases of OO. 91 Although the overwhelming majority of OO-associated mesenchymal tumors have been reported as simply "garden variety" soft tissue and bone tumors of various types (eg, hemangiopericytoma, hemangioma, giant cell tumor, osteoblastoma), it has been recognized by certain investigators that many of these tumors are, in fact, quite distinctive, when carefully evaluated.…”
mentioning
confidence: 99%